KINERJA PPN DI INDONESIA TAHUN 2011-2020 - sulfan sulfan (JURNAL PAJAK INDONESIA, 2021)
Indonesia's VAT performance is still not optimal, so it needs to reset or change the Value Added Tax Act in the Harmonization Regulation Act. The purpose of this study to find out the performance of VAT in Indonesia during the period 2011-2020 is associated with the need for changes to the Value Added Tax Act in the Regulation Harmonization Act. Measurement of VAT performance in Indonesia in this study was measured using the C-efficiency VAT ratio (Ebrill et.al, 2001) and VAT Revenue or VRR ratio (OECD, 2016). Indonesia's VAT performance results during the study period showed the results of 56.51% VAT C-efficiency ratio and VRR of 0.60. The low performance of Indonesian VAT that can be indented results from, among others: the imposition of VAT rates that are lower than standard rates, high threshhold limits, the breadth of objects excluded from the imposition of VAT, and the provision of VAT facilities for certain business activity sectors. Using this research data, changes to the Value Added Tax Act in the Regulatory Harmonization Act can increase the C-efficiency ratio of VAT and VRR by 5.32% and 0.062% respectively.